An investigation into the current knowledge and consumption frequencies of probiotic products amongst UK-based athletes - Myers, E. J. (The Plymouth Student Scientist, 2024)
Growing evidence supports the role of probiotics as modulators of the gut microbiome and subsequent beneficial effects on health, adaptations to exercise, and performance amongst athletes. Despite this, limited literature exists concerning athletes` current understanding or consumption habits of such products. Therefore, the present study aimed to investigate the knowledge and consumption frequencies of probiotic products amongst UK-based recreational and competitive athletes using a three-part online questionnaire. A scoring system based on the number of correct responses to questions regarding probiotics was employed to assess athlete knowledge. Subsequent questions allowed for the collection of data regarding respondents` current consumption habits of different probiotic forms and the reasons for/ against consumption. A total of 238 runners, cyclists, swimmers, or triathletes completed the questionnaire (64% male, 35% female and a mean age of 50 ± 13 years). The results obtained showed that both athletes` knowledge scores (35.6 ± 18.1%) and consumption frequencies of probiotics (2.52 ± 4.14 times/ week) were relatively low. Probiotic knowledge scores were significantly higher among females (6.3 ± 2.8) compared to males (5.5 ± 2.9, p= 0.015) and among triathletes (6.8 ± 2.7) compared to runners (5.4 ± 3.0, p= 0.008) and cyclists (5.6 ± 2.7, p= 0.025). There was also a weak positive association between knowledge and training frequency (rs = 0.151, p= 0.02). Consumption of probiotics in the form of food products was significantly higher than all other forms (p= <0.001). The present study therefore indicates a lack of knowledge surrounding probiotics, accompanied by infrequent consumption, highlighting a potential area for athletic support staff to address when looking to optimise health and performance.